Martial Law as Philippine trauma group culture, the sacred, and impunity in three memoirs - Martin, Jocelyn (2018)
This article argues that Ferdinand Marcos’s martial law regime can be labelled as traumatic based on studies that link the regime’s practices with victims manifesting signs of posttraumatic stress disorder (PTSD). An examination of martial law in the Philippines enriches cultural memory and trauma studies by supporting genres other than (post)modern fiction such as memoir-writing and poetry; by explaining the notion of kapwa, which considers group culture in processes of healing; by putting forward the value of the sacred rather than the Western secular way of “healing”; and, lastly, by underscoring that resolution remains questionable, especially in societies of impunity.
Keywords: Post-traumatic stress disorder; Trauma; Narration (Rhetoric); Martial law; Marcos, Ferdinand E. (Ferdinand Edralin), 1917-1989